Profil Keterampilan Proses Sains Siswa Kelas V SD Inpres Unggulan BTN Pemda Kota Makassar Melalui Penerepan Model Pembelajaran Predict Observe, Discuss, Explain (PODE) - Muhammad Irfan; Syahrani Syahrani (Publikasi Pendidikan, 2018)
This study objective is to determine how the description of the skills of science process skills of grade V students of Primary Inpres superior of BTN PEMDA through the application of Learning Model Predict Observe, Discuss, and Explain (PODE). This research is designed in descriptive form to explain exactly what kind of science classroom process skill V SD Inpres superior BTN PEMDA Makassar City. The use of descriptive method aims to get an overview of the skills of science process students in grade V SD Inpres Superior of BTN PEMDA in depth, detailed and intact. The type of data taken is descriptive quantitative data type, where the data is taken from direct observation by the researcher related to science process skill of grade V SD Inpres Superior of BTN PEMDA. The results of the research are: 1) the ability to observe is categorized well; 2) the ability to make predictions / hypotheses is categorized well; 3) the ability of the child to experiment is categorized as good; 4) the ability to draw conclusions and report the observed results are adequately categorized. Overall student process skills can be categorized well although there are still some aspects that need to be improved